Is alteration of the occlusal plane stable with isolated nasomaxillary fixation of the Le Fort I osteotomy?. Issue 7 (July 2020) - Susarla, S.M.; Ettinger, R.E.; Preston, K.; Kapadia, H.; Egbert, M.A.
Abstract: The purpose of this work was to evaluate the stability of maxillary position in the setting of occlusal plane rotations in bimaxillary surgery with rigid fixation of the mandible and bilateral nasomaxillary fixation at the Le Fort I level. This was a retrospective assessment of patients undergoing bimaxillary surgery for the correction of dentofacial deformities with occlusal plane alterations. Demographic measures assessed included age, sex, history of craniofacial anomaly, segmental maxillary osteotomy, and maxillary bone grafting. Cephalometric measures assessed included occlusal plane rotation (clockwise (CWR) or counterclockwise (CCWR)), angular measurements of maxillary and mandibular position (SNA, SNB, and ANB), and occlusal plane angle (occlusal plane to corrected Frankfort horizontal); these were assessed preoperatively (T0) and immediately (T1), 6 weeks (T2), and 1 year postoperative (T3). Descriptive and bivariate statistics were computed; P ≤ 0.05 was considered significant. Thirty-six patients were included as study subjects (mean age 18.6 ± 1.8 years; 17 (47.2%) female); 27 (75%) had a primary diagnosis of craniofacial anomaly. Eleven patients (30.6%) had segmental maxillary osteotomies; 10 patients (27.8%) had simultaneous maxillary bone grafting. Twelve patients underwent CCWR; 24 patients underwent CWR. No patient required repeat surgery for malocclusion or relapse; there were no malunions or non-unions during follow-up. For CCWR patients, the mean occlusal plane change from preoperative to postoperative was 5.8 ± 2.8°, remaining stable at 1 year postoperative (ΔT3–T1 1.6 ± 1.0°, P > 0.05). For CWR patients, the mean occlusal plane rotation was 4.5 ± 2.2°, remaining stable at 1 year postoperative (ΔT3–T1 1.1 ± 0.9°, P > 0.05). In patients undergoing bimaxillary surgery for occlusal plane rotation, two-point fixation of the Le Fort I osteotomy resulted in a stable maxillary position at 1 year postoperative.